2022
DOI: 10.1002/suco.202100918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of macro synthetic fiber reinforced concrete at elevated temperatures: A systematic review and meta‐analysis

Abstract: The current infrastructure boom combined with the latest outcomes from 26th UN Climate Change Conference of the Parties (COP 26) seeking a carbon neutral society by 2050 have driven the increasing need for sustainable alternatives to be considered in construction. One such alternative is macro synthetic fibers, which have been gaining acceptance on major infrastructure projects. However, only limited uptake has occurred in permanent structures, due to a lack of knowledge around the behavior of macro synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Existing research [47][48][49][50][51] shows that the splitting tensile damage of SFRC was closely related to the concrete matrix strength, steel fiber content and type. Previous studies showed 52 that the steel fiber undertook the main tensile stress after the concrete matrix was destroyed.…”
Section: Prediction Methods Of Splitting Tensile Strengthmentioning
confidence: 99%
“…Existing research [47][48][49][50][51] shows that the splitting tensile damage of SFRC was closely related to the concrete matrix strength, steel fiber content and type. Previous studies showed 52 that the steel fiber undertook the main tensile stress after the concrete matrix was destroyed.…”
Section: Prediction Methods Of Splitting Tensile Strengthmentioning
confidence: 99%
“…The success of conventional FRC has led to the development of a wide range of advanced fiber-reinforced cementitious materials. In recent years, the use of FRC has increased in mainstream construction, despite its decades-old history of introduction [ 8 ]. The use of concrete in structural applications exceeds 50% in developed countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, it was possible to control the crack width and improve the load-bearing capacity of beams by applying SHCC and HSRS bars. Additionally, Kamal et al [ 8 ] applied ultra-high-performance strain-hardening cementitious composites (UHP-SHCC) to RC beams as a tensile-strengthening material. Under flexural loading, UHP-SHCCs achieved significant load-carrying capacity improvements.…”
Section: Introductionmentioning
confidence: 99%